Nurse-led preprocedural Valsalva maneuver training with a maximal expiratory pressure device during transesophageal echocardiography in South Korea: a quasi-experimental study - Kyoungmin Kim; Yoonju Lee; Sanghyun Lee (Journal of Korean Biological Nursing Science, 2026)
Purpose: This study examined the effects of preprocedural Valsalva maneuver (VM) training using a maximal expiratory pressure (MEP) device on VM performance and patient discomfort during transesophageal echocardiography (TEE). Methods: This study used a time-lagged, posttest-only, nonequivalent control group quasi-experimental design. A total of 129 patients undergoing TEE were included in the final analysis, including 67 in the control group and 62 in the intervention group. The control group received written educational materials and standardized verbal instructions, whereas the intervention group received preprocedural VM training with real-time feedback using an MEP device. Analysis of covariance was additionally performed to adjust for potential confounders, including age, sex, education level, and previous endoscopy experience. Results: The number of attempts required for successful VM was significantly lower in the intervention group than in the control group (F = 45.07, p < .001). The VM success rate was higher in the intervention group (F = 51.52, p < .001), and interatrial septal excursion was greater in the intervention group (F = 32.46, p < .001). Nurse-observed discomfort was significantly lower in the intervention group (F = 21.73, p < .001), whereas patient-reported discomfort did not differ significantly between groups (F = 0.15, p = .701). Conclusion: Nurse-led preprocedural VM training using an MEP device may promote more effective VM performance and help reduce observable discomfort during TEE. These findings suggest that preprocedural VM training with real-time feedback may enhance patient cooperation and improve procedural efficiency.Trial Registration: Clinical Research Information Service (CRIS), KCT0008944.